Facile synthesis of flower-like NixCo3-xO4 (0≤x≤1.5) microstructures as high-performance electrode materials for supercapacitors. (20th January 2017) - Che, Hongwei; Liu, Aifeng; Mu, Jingbo; Bai, Yongmei; Wu, Chunxia; Zhang, Xiaoliang; Zhang, Zhixiao; Wang, Guangshuo
Abstract: In this reported work, flower-like Nix Co3-x O4 (0 ≤ x ≤ 1.5) microstructures with different Ni/Co molar ratios were synthesized via a facile solvothermal method followed by calcination. Varying the Ni/Co molar ratio in the solvothermal reaction was found to have a significant influence on the microstructures, surface area and electrochemical performances of the resulting flower-like Nix Co3-x O4 products. When the Ni/Co molar ratio was 1:1, the resulting flower-like Ni1.5 Co1.5 O4 as an electrode for supercapacitor exhibited a high specific capacity of 502.8C g −1 at 1 A g −1, and the highest capacity retention of 85.7% can be achieved at a high current density of 10 A g −1 . Moreover, to further demonstrate the practical application of these materials, an asymmetric supercapacitor was also assembled using the the flower-like Ni1.5 Co1.5 O4 as the positive electrode and active carbon as the negative electrode. The asymmetric supercapacitor device delivered a remarkable energy density of 47.5 Wh kg −1 at a power density of 855 W kg −1, showing the great promise of these novel materials for potential applications in energy storage.